Mutagenicity in tradescantia pallida as an indicator of the effect of air pollution and human health - Godoi, Kaline de Souza Pereira; Spósito, Juliana Caroline Vivian; Rocha, Aline Do Nascimento; Candido, Liliam Silvia; Silva, Caio Augusto Mussury; Lemke, Ana Paula; da Silva, Sandra Verza [UNESP]; Scalon, Silvana de Paula Quintão; de Carvalho, Emerson Machado; Mussury, Rosilda Mara (MDPI, 2021)
The present study aims to relate the micronucleus frequency in Tradescantia pallida to environmental factors and cardiorespiratory diseases to infer the effect of air pollution. The number of hospitalizations, diseases cases, frequency of micronuclei in plants, environmental variables, altitude, and vehicle traffic in cities of Mato Grosso do Sul were evaluated due to the high flow that surrounds agribusiness. The frequency of micronuclei decreased with the increase in relative humidity, while the altitude did not influence the mutagenicity or genotoxicity of the evaluated plants. The municipalities with micronucleus frequencies above 200 had the highest number of vehicle and cardiorespiratory diseases. Biomonitoring data obtained in cities throughout the year indicate that the number of cardiorespiratory diseases was probably due to vehicular pollution, which is evidenced by the increased frequency of micronuclei in T. pallida.
Keywords: Cardiorespiratory disease; Frequency of micronuclei; Genotoxicity; Hospitalizations; Mutagenicity; TRAD–MCN